Dynamic characteristic of multirecess externally pressurized oil journal bearing - Ghosh M.K. (My University, 2025)
This paper describes a theoretical analysis of the dynamic behaoior of multirecess externally pressurized oil journal bearings for a nonrotating journal subjected to plane harmonic vibrations. The generalized Reynolds' equation for a finite bearing has been solved using perturbation theory. Stiffness and damping characteristics of a capillary compensated bearing are given. © 1978 by ASME.